Analisis Pembelajaran di Sekolah Indonesia Kuala Lumpur (SIKL) dalam Upaya Mengembangkan Minat dan Bakat Siswa di Era New Normal - Eva Luthfi Fakhru Ahsani; Siti Nur Elisa Lusiana; Umi Mardliyah; Heni Noor Humaidah; Roihatun Nurus Safaah (Jurnal Kependidikan, 2020)
The purpose of this study was to analyze learning at the Kuala Lumpur Indonesian School (SIKL) in an effort to develop student talent interest during the new normal. The research approach in this study uses a qualitative research type. The data collection method is in the form of an analysis that is interview and documentation in the Kuala Lumpur Indonesian School (SIKL). The data analysis technique used descriptive-qualitative. The results of the study explained that the concept of learning at the Kuala Lumpur Indonesian School (SIKL) was carried out with two models, namely BDR (learning from home) and BDS (learning at school). For the BDR learning model (learning from home) it is carried out online accompanied by parents using the classroom application, video, converence, telephone or live chat, zoom or via the whatsapp group. While the BDS learning model (learning at school) uses standard operating procedures (SOP) including 3M, washing hands, wearing masks and maintaining distance. Efforts to develop students 'interests and talents at Sekolah Indonesia Kuala Lumpur (SIKL) in the new normal era teachers pay more attention to students, Collaboration between parents and teachers plays an important role in developing students' interests and talents, providing motivation for students to develop their interests and talents , schools must facilitate facilities for students to develop their interests and talents. Finally, teachers hold various kinds of competitions as a place to develop their interests and talents.